Relación entre la forma de la cara y los incisivos centrales superiores para la selección adecuada de dientes artificiales - Pazmiño Villacís, Patricio David (2019)
The objective of this research was to determine the relationship between the shape of the face and the upper central incisors for the proper selection of artificial teeth. We observed facial contours and maxillary central incisors based on the statement of the harmonic theory of Williams, which shows the connection between the facial lines and the tooth type, these geometric shapes are: square, triangular and oval. The population was composed of 44 intraoral photographs and 44 extraoral photographs, which were donated by the students of the sixth and eighth semesters of the Dentistry career of the National University of Chimborazo. The technique used was the observation and its instrument the observation card in which the geometric shapes of the face were determined in relation to the upper central incisors. At the end of this investigation the shape of the most prevalent face was the oval one with 45.5% followed by the triangular and square shape with 27.3% respectively. As for the upper central incisors, the square shape together with the triangular had 40.9% respectively and the oval shape 18.2%. Where it could be concluded that the relationship between the shape of the face and the upper central incisors was not significant, with a P = 0.028, determined to be statistically proven the inexistence of a relationship between the shape of the face and the central incisors maxillae for the proper selection of artificial teeth in our environment.